2007
DOI: 10.1093/jnci/djm065
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Fruit and Vegetable Intake and Risk of Prostate Cancer

Abstract: High intake of cruciferous vegetables, including broccoli and cauliflower, may be associated with reduced risk of aggressive prostate cancer, particularly extraprostatic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
193
1
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(201 citation statements)
references
References 48 publications
1
193
1
6
Order By: Relevance
“…Only one24 out of the five5, 8, 9, 24, 25 studies that have assessed the association between citrus fruit and prostate cancer risk has also found a significant inverse association, and no association between circulating concentrations of the citrus biomarker β ‐cryptoxanthin and prostate cancer risk was observed in a pooled analysis of 10 prospective studies 26. Our non‐significant associations between several vegetable subtypes and risk of prostate cancer are in line with previous prospective studies which have also found no association between overall prostate cancer risk and cruciferous9, 12, 27 or leafy vegetable intake 8, 9, 28, 29.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one24 out of the five5, 8, 9, 24, 25 studies that have assessed the association between citrus fruit and prostate cancer risk has also found a significant inverse association, and no association between circulating concentrations of the citrus biomarker β ‐cryptoxanthin and prostate cancer risk was observed in a pooled analysis of 10 prospective studies 26. Our non‐significant associations between several vegetable subtypes and risk of prostate cancer are in line with previous prospective studies which have also found no association between overall prostate cancer risk and cruciferous9, 12, 27 or leafy vegetable intake 8, 9, 28, 29.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, special attention has been paid to the possible protective effect of the consumption of cruciferous vegetables and tomatoes on prostate cancer, although to date results are not conclusive 12, 13. Regarding fruit consumption, most prospective studies have found no association with prostate cancer development 4, 5, 6, 9. The latest meta‐analysis from the World Cancer Research Fund/American Institute for Cancer Research (WCRF/AICR) stated that no conclusion could be reached on whether fruit and vegetable consumption is associated with prostate cancer risk3; this meta‐analysis did not differentiate between grade and stage of the disease (stage and grade are grouped together as advanced/high grade or non‐advanced/low grade), and only included a limited number of fruit and vegetable subtypes (namely cruciferous vegetables and tomatoes); therefore, more studies are needed.…”
mentioning
confidence: 99%
“…In contrast, several studies indicate that cabbages may have specific health-promoting properties, e.g. as a prophylactic for cancer, above the general health benefits obtained from eating fruits and vegetables (22)(23)(24)(25)(26) . Cabbages have a high content of vitamin K, antioxidants, dietary fibre, folate, and of several carotenoids and glucosinolates that are not found in other foods.…”
Section: Fruits and Vegetablesmentioning
confidence: 99%
“…Conversely, regular physical activity (2) and the consumption of fruits and vegetables, particularly those belonging to the cruciferous family, may reduce this risk (3)(4)(5). Indeed consumption of cruciferous vegetables has been reported to reduce the risks of prostate cancer by 40% (3,4), extraprostatic prostate cancer by up to 40% (6), and progression by 59% (7) in men diagnosed with nonmetastatic disease.…”
Section: Introductionmentioning
confidence: 99%